Helicobacter pylori eradication and gastric cancer prevention in a pooled analysis of large-scale cohort studies in Japan - Ono, Ayami; Tanaka, Shiori; Sawada, Norie; Goto, Atsushi; Tsugane, Shoichiro; Muraki, Isao; Yamagishi, Kazumasa; Sasaki, Yu; Abe, Yasuhiko; Kayama, Takamasa; Ueno, Yoshiyuki; Saito, Eiko; et al. (Scientific reports, 2025)
Helicobacter pylori ( H. pylori) infection is an established cause of gastric cancer. Although H. pylori eradication is suggested to decrease gastric cancer risk, this has not been fully investigated in general populations. This analysis included 48,530 Japanese men and women aged 40–74 years from four cohort studies. At baseline, the participants provided a self-reported eradication history and serum anti- H. pylori IgG titers and the results of a pepsinogen (PG) test. We examined the association between eradication history and gastric cancer risk considering H. pylori positivity and PG testing using Cox proportional hazards regression models. From 2010 to 2018, 649 gastric cancer cases were diagnosed. Compared with those who were negative for both H. pylori and PG test as a reference, gastric cancer risk was 5.89 times higher (95%CI: 4.41–7.87) in those who were H. pylori -positive and/or PG test-positive and with no eradication at baseline. Gastric cancer risk among those who underwent eradication before baseline decreased after a temporal increase in risk following eradication (baseline to < 1y: HR 1.74, 95%CI 1.18–2.57; 1y to < 6y: HR 0.81, 95%CI 0.59–1.11; ≥ 6y: HR 0.44, 95%CI 0.28–0.68). In this large Japanese general population, H. pylori eradication was associated with a long-term reduction in gastric cancer incidence.